Prevalence of peripheral arterial disease and association with cardiovascular risk factors in patients with end-stage kidney disease in a hospital in Nigeria - Abu, Sadiq; Olatise, Olalekan O; Asaolu, Stephen O; Daniel, Gloria; Waziri, Bala (African Journal of Nephrology, 2022)
Introduction: Peripheral arterial disease (PAD) is not uncommon among patients with end-stage kidney disease (ESKD), but it is usually under-reported. Moreover, PAD is a strong independent risk factor for cardiovascular disease in persons with chronic kidney disease (CKD). The aim of this study was to evaluate the prevalence of PAD and its association with cardiovascular risk factors in Nigerian patients with ESKD. Methods: This was a retrospective investigation of 122 subjects with ESKD on haemodialysis (HD), who were worked up for renal transplantation at Zenith Medical and Kidney Centre in Gudu, Abuja, Nigeria from February 2020 to March 2021. Data were obtained from the electronic medical records of the hospital and included sex, age, body mass index, history of diabetes, hypertension (HTN), duration of CKD, length of dialysis, lipid profile and lower limb Doppler ultrasound. Cardiovascular risk, measured as atherogenic index (AI), was calculated using the formula log (TG/ HDL-C), where TG = triglyceride and HDL-C = high-density lipoprotein cholesterol. Data analysis was performed using SPSS version 20. Continuous variables were expressed using measures of central tendency whereas categorical variables were expressed as frequency (percentages). Bivariate analysis was used to establish association between each variable, PAD and AI. A chi-square test was used to examine the relationship between categorical variables; a P value <0.05 was considered statistically significant. Results: Male subjects accounted for 81.1% of the study population. The median duration of CKD was 8 months (range 1–96 months) and the mean duration of dialysis was 10 ± 1.1 months. HTN was the commonest comorbidity factor in these subjects with 98 (80%) hypertensive with a median duration of the condition of 5 years (range 1–32 years); diabetes mellitus (DM) accounted for 44 (36%) patients with a median duration of 15 years (range 1–36 years). The prevalence of PAD among patients with ESKD was 48.4%. AI was associated with dialysis duration. The association between duration of CKD and PAD was positive and significant (rho = –0.245, P = 0.007). Conclusion: PAD was highly prevalent among patients with ESKD and remains one of the most potent risk markers for cardiovascular morbidity in patients with CKD. Patients with CKD should routinely be examined for PAD and the longer ESKD patients stay on dialysis, the greater the risk of developing cardiovascular disease. Screening for PAD and prompt treatment would be beneficial for pretransplant patients before the procedure.